Morphological and histological features of abdominal glands in Japanese marten (Martes melampus) - Jumpei Tomiyasu; Mimi Arakaki; Tetsuhito Kigata; Akio Iwashita; Wataru Tonomori (PLoS ONE, 2025)
The Japanese marten ( Martes melampus ) is a solitary mustelid species with a strict territorial space that might be maintained by scent marking. However, whether Japanese martens have scent glands that secrete chemical signals remains unknown. We aimed to clarify whether the abdominal glands in these animals secrete chemical signals and, if so, to characterize their morphological and histological features. We investigated nine Japanese martens (eight M. m. tsuensis and one M. m. melampus ) that were all roadkilled. Regardless of sex, season, and subspecies, they all had abdominal glands located at the rostral aspect of the penis or vagina, and brown secretions were evident on the skin area. Enlarged sebaceous and small apocrine glands were spread mostly throughout the abdominal glands. Obviously enlarged, specialized glands were located in the caudal and medial areas of the abdominal glands. The specialized and sebaceous gland cells were connected through a duct at the border between them. This suggested that the specialized gland cells were derived from the sebaceous type. However, eosin staining of the specialized gland cells possessing a nucleus was strongly positive for cytoplasm, whereas that of the sebaceous gland cells was weakly positive. Moreover, the specialized gland cells were weakly stained with Oil Red O, whereas the sebaceous gland cells were strongly stained. Thus, the secretory mechanism of the abdominal specialized glands may not be holocrine like sebaceous glands. In conclusion, Japanese martens had characteristic abdominal glands with developed sebaceous and specialized glands.